178k views
1 vote
Write the difference of expressions as a and simplify it: 17x−13y+8 and 20x+6y._
_-_=_

User Inch High
by
5.5k points

2 Answers

4 votes

Solution:

The difference in expression is written with a - sign in between

The difference of 17x-13y+8 and 20x+6y is :

17x-13y+8-( 20x+6y)

There is a - sign outside the bracket ,if we open the bracket the signs will change.

17x-13y+8-(20x+6y)

=17x-13y+8-20x-6y

=17x-20x-13y-6y+8( Rearranging the terms)

=-3x-19y+8(Simplifying like terms)


User Ilya Sereb
by
5.7k points
4 votes

Answer:


=(17x-13y+8)-(20x+6y)=-3x-19y+8

Explanation:

Given : Expressions
17x-13y+8 and
20x+6y

To find : Write the difference of expressions and simplify it ?

Solution :

The difference means subtracting the two expression,

Let
17x-13y+8 ....(1)


20x+6y ....(2)

Subtract (2) from (1),


(17x-13y+8)-(20x+6y)

Simplifying it,


=17x-13y+8-20x-6y


=-3x-19y+8

Therefore,
=(17x-13y+8)-(20x+6y)=-3x-19y+8

User Vianna
by
5.1k points